Measurement and drawing inventory of wooden architecture monuments in the renovation process – problems and proposal of standardization - Prarat, Maciej; Schaaf, Ulrich (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
Nowadays, measurement and drawing inventory of architecture monuments is prepared according to very different standards. Thus, in this paper the question about the reasons of such condition will be raised. Subsequently, different measurement methods will be presented, from the manual ones, then tachymetry and photoplan, up till laser scanning technique. There will also be discussed basic purposes at which the documentation should serve. Finally, in the conclusion, the authors will propose three-step standardization of the inventory due to the accuracy degrees, scale and drawing content.